Book and book groups - Hagenhoff, Svenja (Handbook of Media and Communication Economics, 2023)
The book in the form of the codex known today is considered the oldest mass medium. The article first attempts to grasp this medium detached from its material nature with the help of the approaches of various disciplines and contours it as an indeterminable form of “reading medium.” Over three major periods – the manuscript era, printing with movable type, and the age of digitization – the nature of the production, the product, and the publishing system are traced and characterized. For the current German-language book market, the structures of the two value-added stages of production and distribution are described and the institutions that directly or indirectly influence the system of book media communication are elaborate
Keywords: Books; book industry; book markets